THE SOCIOTECH LEARNING MODEL TO OVERCOME THE LOW STUDENTS EMPLOYABILITY SKILLS - Nuryake Fajaryati; Budiyono Budiyono; Muhammad Akhyar; Wiranto Wiranto (PEDAGOGIA, 2023)
Employability skills is an essential aspect for job seekers because employers and the world of work need it; however, many job seekers have the low employability skills. This study aims to reveal the need of SocioTech learning models through blended learning to overcome low students employability skills. The  descriptive research used to determine the level of employability skills among students, the analysis used the descriptive statistical analysis technique, and it used literature study to examine the SocioTech learning model. The results of the study showed the overall assessment of employability skills, revealing 31.58% of students to have average employability skills; 44.74% of students in the fair category; 23.68% of students classified as poor. Recommendation of SocioTech learning model through blended learning to improve employability skills consisted of six stages: 1) determining the topic of problems and groups through dialectics online and face to face (f2f); 2) planning investigations through collaboration and dialectics online and f2f; 3) conducting investigations through collaboration and dialectics online and f2f; 4) planning presentations through collaboration and dialectics online and f2f; 5) making presentations through collaboration, reflection, and dialectics online and face to face; and 6) evaluating group results online and f2f.